Principal Leadership Strategy in Improving Teacher Quality at SLB Smart School Pacet Mojokerto - Hoririah, Hoiri; Amalia Nasucha, Juli; Yuliarsih, Tiara (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Education is a fundamental right of every individual regardless of background, including physical or psychological conditions. Special schools (SLB) serve as educational institutions for children with special needs, one of which is SLB Smart School Pacet Mojokerto. This study aims to describe the principal’s strategies in improving the quality of teachers’ human resources and to identify the supporting and inhibiting factors in implementing these strategies. This research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, involving the principal, teachers, and school staff as research subjects. The results indicate that the principal implemented structured strategies through teacher programs (lesson planning, teaching and learning activities, professional development, workshops, and tutoring), task distribution (job desk), and learning evaluation (planning, teaching, assessment, communication, and professional development). The inhibiting factors include the limited educational background of teachers in special education and the lack of optimal discipline among some teachers, while the supporting factors consist of teacher competence development programs and the principal’s managerial support. Overall, the principal’s strategies significantly contributed to improving the quality of teachers’ human resources, which had a positive impact on educational services for children with special needs at SLB Smart School Pacet.